A Development of Community Participation Model in Road Traffic AccidePrevention Management at Raikhing Sub-district Sampran District Nakhon Pathom Province - Chatdokmaiprai, Kannikar; Khaonuan, Boonruang; Singchungchai, Phechnoy; Roojanavech, Sasitorn; Srinopakhun, Pimnipa; Tantapong, Usa (NU Journal of Nursing and Health Sciences, 2025)
This action research aimed to analyze the situation of road traffic accidents, develop, trial use, and evaluate the road traffic accident management model in Rai Khing Subdistrict, Nakhon Pathom Province. The sample groups were 1) the community leader group and stakeholder consisting of 10 persons, and 2) the student group, consisting of 60 students. The research instrument used were five tools that drive the mechanism of the Road Safety Center to the outcomes, and a questionnaire of knowledge, perceived sensitivity, perceived severity, perceived benefits, perceived barriers, and behavior in preventing road traffic accident. Qualitative data was analyzed by content analysis. The mean differences of the score of knowledge, perceptions in each area, and behavior in preventing road traffic accidents between the experimental group and the control group were compared using the independent t-test.The research results found that: 1) The most common traffic accidents in Raikhing sub-district were caused by motorcycles, at 65.7%. Majority (35.5%), were aged 36-60 years and found in adolescents aged 15-18 years at 8.4%. Most of the accident (32.3%) occurred during, 6.00-9.59 pm. 2) The community participation model has 3 aspects: 2.1) Developing the potential of youth in terms of knowledge, perceived sensitivity, perceived severity, perceived benefits, perceived barriers, and behavior in preventing road traffic accident. 2.2) Preventing accidents at risk points, and 2.3) Creating a traffic accident prevention mechanism by the community leader team organizing a rescue team that can reach victims in a timely manner. 3) In the evaluation of the model development phase, it was found that after the training, the experimental group of students had average scores in knowledge, perceived sensitivity, perceived severity, perceived benefits, perceived barriers and behavior in preventing road traffic accident significantly higher than the ones of control group at the .05 level.This study suggests that this community participation model should be further developed in other sub-districts.This study suggests that community leaders, and stakeholders should create a concrete working model, and this community participation model should be further developed in other sub-districts.